High-dispersion nitrogen-doped copper-based catalyst as well as preparation method and application thereof
Through the preparation of a high-dispersible nitrogen-doped copper-based catalyst, the carbon source and nitrogen source are combined as a support, the problems of catalyst dispersion and high activation temperature are solved, and the efficient hydrogen production reaction of methanol aqueous liquid phase reforming is achieved, thereby improving the The hydrogen production rate and hydrogen selectivity reduce the reaction temperature and cost.
Patent Information
- Application Number
- CN202411525882.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing catalysts have problems such as low dispersion, high activation and high reaction temperature in the methanol aqueous liquid phase reforming hydrogen production reaction, which limits their application in the liquid phase reforming hydrogen production.
Using a highly dispersed nitrogen-doped copper-based catalyst, the carbon source is combined with the nitrogen source as a support, and Cu as an active substance, the growth of copper nanoparticles is inhibited through complexing and fixing, and the dispersion and activity of the catalyst is improved. The preparation method includes Dissolved copper, carbon and nitrogen sources into a mixed solution, evaporated and concentrated to form a gel, and activated under a pyrolysis treatment and reduction atmosphere.
The high dispersion and low activation temperature of copper in the catalyst are achieved, the hydrogen production rate and hydrogen selectivity of methanol liquid phase reforming hydrogen production reaction are improved, and the reaction temperature and cost are reduced.
Smart Images

Figure CN119236995A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and more specifically, to a highly dispersed nitrogen-doped copper-based catalyst and a preparation method and application thereof. Background Art
[0002] Hydrogen energy has become an extremely attractive clean energy source due to its cleanliness, high calorific value, and diverse forms of utilization. It has broad application prospects, but it still faces severe challenges in the efficient storage and transportation of hydrogen. The main sources of traditional hydrogen production are fossil fuels (coal, natural gas, oil) and water electrolysis. Although the use of fossil fuels to produce hydrogen is cheap, it is inconsistent with the country's sustainable development strategy; water electrolysis to produce hydrogen consumes huge amounts of electricity and requires higher costs.
[0003] Liquid hydrogen-containing chemicals represented by methanol have high hydrogen storage density per unit volume and good chemical stability. They are easy to store and are ideal liquid hydrogen storage molecules. From the existing methods of producing hydrogen from methanol, there are three main categories: steam reforming, liquid phase reforming and photocatalysis. The steam reforming device is large, the reaction temperature is high, the energy consumption is high, the carbon monoxide concentration in the product is high, and it is easy to undergo methanation reaction to produce too much methane, the hydrogen production rate is low, and the resulting hydrogen selectivity is poor. The traditional thermal catalytic liquid phase conversion to prepare methanol has relatively mild reaction conditions, and the cost of hydrogen production is lower than that of hydrogen production by electrolysis of water. The core lies in the selection and application of catalysts. However, most of the existing catalysts are precious metals (Pd, Pt). Although they have high hydrogen production selectivity, they are expensive and have poor economy, which limits their large-scale application.
[0004] The prior art discloses a copper-based catalyst for hydrogen production from methanol-water liquid phase reforming, which uses Cu as the main active component and nitrogen-containing chitosan as the carbon source to prepare a nitrogen-doped carbon-coated copper-based catalyst. The copper-based catalyst is applied to the methanol-water liquid phase reforming hydrogen production reaction. Compared with the traditional carbon-coated copper-coated methanol-water liquid phase reforming hydrogen production catalyst, the CO selectivity in the product is not higher than 0.03%, but its hydrogen production rate is 34μmol H2 / g cat / s, which cannot meet the application needs. Therefore, the development of high-activity copper-based catalysts with good dispersibility and low activation temperature for hydrogen production from methanol liquid phase reforming has become an urgent problem to be solved. Summary of the invention
[0005] The present invention aims to overcome the technical problems in the prior art of preparing copper-based catalysts for alcohol reforming to produce hydrogen, such as low dispersibility, high activation and reaction temperatures resulting in low catalytic activity of the catalyst, and provide a highly dispersed nitrogen-doped copper-based catalyst.
[0006] Another object of the present invention is to provide a method for preparing a highly dispersed nitrogen-doped copper-based catalyst.
[0007] Another object of the present invention is to provide an application of a highly dispersed nitrogen-doped copper-based catalyst in hydrogen production by liquid phase reforming of alcohols.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0009] A highly dispersed nitrogen-doped copper-based catalyst comprises a carrier and an active metal component loaded on the carrier. The carrier of the copper-based catalyst consists of a carbon source and a nitrogen source, and the active metal component is Cu.
[0010] The highly dispersed nitrogen-doped copper-based catalyst of the present invention uses a carbon source combined with a nitrogen source as a carrier, and Cu as an active substance. When the carbon source and the nitrogen source are combined as a carrier, the rich functional groups on the carrier can be complexed with copper, and the copper can be fixed at the same time, inhibiting the further growth of copper nanoparticles, providing more active sites, and thus improving the dispersibility of copper in the catalyst.
[0011] Preferably, the molar ratio of the carbon source to the nitrogen source of the present invention is 1:(1.5-6).
[0012] If the molar ratio of the carbon source to the nitrogen source in the carrier of the present invention is too high or too low, the particle size of the metal will be too large and the dispersibility will be poor, resulting in a decrease in the catalytic performance of the catalyst.
[0013] The average particle size of copper in the copper-based catalyst of the present invention is 5 to 10 nm.
[0014] Preferably, the average particle size of copper in the copper-based catalyst of the present invention is 5 to 6 nm.
[0015] The loading amount of the active metal component Cu in the copper-based catalyst of the present invention is 30wt% to 60%.
[0016] When the active component loading in the copper-based catalyst of the present invention is too low, the active substances for catalyzing the liquid phase reforming of methanol to produce hydrogen are insufficient, thereby reducing the catalytic activity. However, when the loading exceeds a certain limit, the effect of the increase in the loading on the catalytic activity improvement of the liquid phase reforming of methanol to produce hydrogen gradually weakens. Moreover, when the Cu loading is too high, it is also easy to cause the agglomeration of the active components, thereby reducing the dispersibility of copper in the catalyst.
[0017] The present invention also protects a method for preparing the highly dispersed nitrogen-doped copper-based catalyst, comprising the following steps:
[0018] S1. Dissolve the copper source, carbon source and nitrogen source in proportion to form a mixed solution, stir evenly, evaporate and concentrate to form a gel, and dry to obtain a highly dispersed nitrogen-doped copper-based catalyst precursor; the molar ratio of the copper source, carbon source and nitrogen source in the mixed solution is: 2.5:1:(1.5-6);
[0019] S2. subjecting a highly dispersed nitrogen-doped copper-based catalyst precursor to a pyrolysis treatment at 300 to 500° C. for 2 to 5 hours; and then subjecting the pyrolysis-treated catalyst precursor to an activation treatment in a reducing atmosphere to obtain the highly dispersed nitrogen-doped copper-based catalyst.
[0020] As the molar ratio of the copper source in the mixed solution described in S1 of the present invention increases, the active metal particles will gradually increase in size, resulting in a decrease in the dispersibility of the catalyst and also affecting the catalyst's selectivity for hydrogen.
[0021] In S1 of the present invention, the stirring temperature is 80-90° C., the stirring rate is 300 rpm, the drying temperature is 80-90° C., and the drying time is 12-24 h.
[0022] When the pyrolysis temperature of the present invention is less than 300°C, the performance will increase with the increase of temperature. When the temperature is greater than 500°C, the particle size of the active metal particles will increase, agglomeration will occur, the dispersion will deteriorate, and the carbon monoxide and methane content in the product will increase, and the selectivity of hydrogen will decrease.
[0023] The pyrolysis treatment atmosphere in S2 described in the present invention is a nitrogen atmosphere.
[0024] The activation treatment under reducing atmosphere in S2 of the present invention is to reduce the highly dispersed nitrogen-doped copper-based catalyst precursor after pyrolysis treatment at 300° C. for 2 hours in a hydrogen atmosphere; the hydrogen flow rate is 50 mL / min.
[0025] Since the functional groups of the composite carbon material used to prepare the highly dispersed nitrogen-doped copper-based catalyst precursor can chelate copper, the agglomeration of copper can be reduced. Therefore, the activation treatment of the highly dispersed nitrogen-doped copper-based catalyst precursor in the present invention is carried out at a relatively low temperature, which can further ensure the dispersibility of the obtained copper-based catalyst, and the low activation temperature also reduces the energy consumption during the catalyst reduction process.
[0026] The copper source in S1 of the present invention is selected from one or more of copper nitrate, copper chloride, copper sulfate and copper acetate.
[0027] The carbon source in S1 of the present invention is selected from one or more of starch, glucose, cyclodextrin and citric acid.
[0028] The nitrogen source in S1 of the present invention is selected from one or more of ornithine, glycine, citrulline and arginine.
[0029] The present invention also protects the use of the highly dispersed nitrogen-doped copper-based catalyst in catalyzing the liquid-phase reforming of alcohols to produce hydrogen, and the specific application method is as follows:
[0030] A highly dispersed nitrogen-doped copper-based catalyst is mixed with alcohols and water, and reacted under anaerobic conditions and heated to 190-230°C for 1 hour to obtain hydrogen.
[0031] The alcohols described in the present invention are selected from one or more of methanol, ethanol and propanol.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The invention provides a highly dispersed nitrogen-doped copper-based catalyst, wherein Cu is used as an active substance, and a carbon source combined with a nitrogen source is used as a carrier to improve the dispersibility of copper in the catalyst.
[0034] The highly dispersed nitrogen-doped copper-based catalyst of the present invention is used to catalyze the hydrogen production reaction of methanol-water liquid phase reforming. The hydrogen production reaction temperature is 190-230°C, which is lower than 250°C in the prior art, and its hydrogen production rate is not less than 97.7 μmol H2 / g cat / s, CO content is not higher than 0.0084%, CH4 content is not higher than 0.004%, and it has excellent hydrogen selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 This is the XRD pattern of the highly dispersed nitrogen-doped copper-based catalyst prepared in Example 1 of the present invention;
[0036] Figure 2 This is a transmission electron microscope image of the highly dispersed nitrogen-doped copper-based catalyst prepared in Example 1 of the present invention;
[0037] Figure 3 This is a thermogravimetric analysis curve of the highly dispersed nitrogen-doped copper-based catalyst prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] The present invention will be further described below in conjunction with specific embodiments, but the embodiments do not limit the present invention in any form. Those skilled in the art will understand that the changes, replacements, and improvements made to the present invention still belong to the protection scope of the present invention. Unless otherwise specified, the raw material reagents used in the embodiments of the present invention are conventionally purchased raw material reagents.
[0039] Source of raw materials: The reagents used in the examples and comparative examples of the present invention were purchased from Aladdin Reagent Co., Ltd.
[0040] Example 1
[0041] The present embodiment provides a highly dispersed nitrogen-doped copper-based catalyst, which contains a carrier and an active metal component loaded on the carrier, wherein the carrier of the copper-based catalyst is composed of a carbon source and a nitrogen source, wherein the molar ratio of the carbon source to the nitrogen source is 1:3; the active metal component is Cu, and the loading amount is 50.8wt%; the average particle size of copper in the copper-based catalyst is 5.8nm.
[0042] The method for preparing the highly dispersed nitrogen-doped copper-based catalyst comprises the following steps:
[0043] S1. Copper nitrate, cyclodextrin, polyether and arginine are prepared into a solution in proportion, wherein the molar ratio of copper nitrate, cyclodextrin and arginine in the solution is 2.5:1:3; the solution is stirred at 300 rpm and slowly evaporated at 80°C for 24 hours to form a gel. The solution is dried in a drying oven at 80°C for 12 hours and taken out to obtain a highly dispersed nitrogen-doped copper-based catalyst precursor.
[0044] S2. Grind the highly dispersed nitrogen-doped copper-based catalyst precursor and load it into a corundum crucible, perform pyrolysis treatment in a tubular furnace, raise the temperature to 400°C at a rate of 5°C / min and pyrolyze for 2 hours, and further grind and sieve it after it cools down to room temperature; then reduce the catalyst precursor after pyrolysis treatment at 300°C for 2 hours at a hydrogen flow rate of 50 mL / min to obtain a highly dispersed nitrogen-doped copper-based catalyst.
[0045] Example 2
[0046] The preparation steps and parameters are the same as those in Example 1, except that the Cu loading in the highly dispersed nitrogen-doped copper-based catalyst carrier is 47.2 wt %;
[0047] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the molar ratio of copper nitrate, carbon source and nitrogen source in the S1 solution is 2.2:1:3.
[0048] Example 3
[0049] The preparation steps and parameters are the same as those in Example 1, except that the Cu loading in the highly dispersed nitrogen-doped copper-based catalyst carrier is 51.2 wt %;
[0050] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the molar ratio of copper nitrate, carbon source and nitrogen source in the S1 solution is 2.5:1:1.5.
[0051] Example 4
[0052] The preparation steps and parameters are the same as those in Example 1, except that the Cu loading in the highly dispersed nitrogen-doped copper-based catalyst carrier is 48.9 wt %;
[0053] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the molar ratio of copper nitrate, carbon source and nitrogen source in the S1 solution is 2.5:1:4.5.
[0054] Example 5
[0055] The preparation steps and parameters are the same as those in Example 1, except that the Cu loading in the highly dispersed nitrogen-doped copper-based catalyst carrier is 55 wt%;
[0056] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the molar ratio of copper nitrate, carbon source and nitrogen source in the S1 solution is 2.5:1:1.5.
[0057] Example 6
[0058] The preparation steps and parameters are the same as those in Example 1, except that the average particle size of copper in the highly dispersed nitrogen-doped copper-based catalyst is 5.7 nm;
[0059] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the pyrolysis temperature in S2 is 350° C. and the pyrolysis time is 2 hours.
[0060] Example 7
[0061] The preparation steps and parameters are the same as those in Example 1, except that the average particle size of copper in the highly dispersed nitrogen-doped copper-based catalyst is 7.4 nm;
[0062] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the pyrolysis temperature in S2 is 450° C. and the pyrolysis time is 2 hours.
[0063] Example 8
[0064] The preparation steps and parameters are the same as those in Example 1, except that the average particle size of copper in the highly dispersed nitrogen-doped copper-based catalyst is 8 nm;
[0065] In the step of preparing the highly dispersed nitrogen-doped copper-based catalyst, the pyrolysis temperature in S2 is 500° C. and the pyrolysis time is 3 hours.
[0066] The process parameter changes for preparing highly dispersed nitrogen-doped copper-based catalysts in Examples 1 to 8 are shown in Table 1:
[0067] Table 1 Process parameters and catalyst properties for preparing highly dispersed nitrogen-doped copper-based catalysts in Examples 1 to 8
[0068]
[0069] Comparative Example 1
[0070] The preparation steps and parameters are the same as those in Example 1, except that the carrier of the highly dispersed copper-based catalyst is only carbon and does not contain a nitrogen source. The Cu loading is 42.8 wt%.
[0071] In the step of preparing the highly dispersed copper-based catalyst, S1. copper nitrate and cyclodextrin are prepared into a solution in proportion, and the molar ratio of copper nitrate to cyclodextrin in the solution is 2.5:1.
[0072] Comparative Example 2
[0073] The preparation steps and parameters are the same as those in Example 1, except that the carrier of the highly dispersed copper-based catalyst is only citric acid and does not contain a nitrogen source. The Cu loading is 55 wt%.
[0074] In the step of preparing the highly dispersed copper-based catalyst, S1. copper nitrate and citric acid are prepared into a solution in proportion, and the molar ratio of copper nitrate to citric acid in the solution is 3:1.
[0075] Comparative Example 3
[0076] Commercial copper-zinc-aluminum purchased from the market.
[0077] Performance Testing
[0078] The copper-based catalysts described in Examples 1 to 8 and Comparative Documents 1 to 3 were characterized and their thermal catalytic performance tested.
[0079] The crystal structure of the highly dispersed nitrogen-doped copper-based catalysts described in Examples 1 to 8 was analyzed using an X-ray diffractometer. Figure 1 From top to bottom are the XRD spectra of the copper-based catalysts provided by Comparative Example 1, Example 3, Example 4 and Example 1. Figure 1 It can be seen that the peak area of Cu in the 50.8wt% Cu@NC catalyst provided in Example 1 of the present application is significantly smaller than that of the Cu@C provided in Comparative Example 1 and the Cu@NC containing excess nitrogen content provided in Examples 3 and 4, indicating that the particle size of the active metal Cu in the catalyst provided in Example 1 is significantly smaller than that of the catalysts provided in Comparative Example 1 and Examples 3 and 4, and the excess nitrogen content will increase the particle size of copper and reduce the dispersibility of copper.
[0080] Figure 2 is the transmission electron microscope spectrum of the highly dispersed nitrogen-doped copper-based catalyst obtained in Example 1; Figure 2 It can be seen that the main particle size of the highly dispersed nitrogen-doped copper-based catalyst is 5.8 nm.
[0081] Figure 3 is a thermogravimetric analysis curve of the precursor of the highly dispersed nitrogen-doped copper-based catalyst obtained in Example 1 under a nitrogen atmosphere; Figure 3 It can be seen that the obtained catalyst precursor has the largest heat loss before 300°C, which is attributed to the thermal decomposition of copper nitrate and carbon support; the mass loss after 400°C is relatively gentle, and the mass change of the carbon support is small at this time. Continuing to increase the temperature may further increase the particle size of the metallic copper, thereby reducing the dispersibility of the active component copper. The thermogravimetric analysis curves of the highly dispersed nitrogen-doped copper-based catalysts in Examples 2 to 8 are basically consistent with those in Example 1.
[0082] The performance of highly dispersed nitrogen-doped copper-based catalyst in catalyzing liquid phase reforming of methanol to produce hydrogen was tested.
[0083] The hydrogen production from methanol liquid phase reforming is carried out in a reactor and heated by a heating furnace equipped with a magnetic stirring device. The specific test method is as follows:
[0084] Weigh 50 mg of any catalyst obtained in Examples 1 to 8 and Comparative Examples 1 to 3 and place it in the inner lining of the reactor, and add 20 mL of methanol aqueous solution (methanol and water molar ratio is 1:1). After the reactor is installed, the inert gas is pressurized to 2 MPa, and the gas is repeatedly washed three times to ensure that the air is completely removed. Heat the reaction at 210°C and 2 MPa N2 atmosphere for 1 hour. After the reaction, the gas inside the reactor is collected with an air bag and analyzed by GC to determine the amount of hydrogen produced. The catalytic effects of the catalysts obtained in Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 2.
[0085] Table 2 Catalytic activity of the catalysts obtained in Examples 1 to 8 and Comparative Examples 1 to 3
[0086] catalyst <![CDATA[Hydrogen production rate / (μmolH2 / g cat / s)]]> <![CDATA[H2 Selectivity / %]]> <![CDATA[CH4 Selectivity / %]]> CO selectivity / % Example 1 97.70 99.91 0.0034 0.0845 Example 2 87.61 99.92 0.0044 0.074 Example 3 32.29 99.985 0.0111 0.118 Example 4 17.87 99.86 0.0195 0.078 Example 5 1.38 99.53 0.0248 0.442 Example 6 60.40 99.93 0.00342 0.084 Example 7 76.83 99.93 0.011 0.055 Example 8 77.26 99.93 0.011 0.055 Comparative Example 1 38.05 99.90 0.0075 0.091 Comparative Example 2 25.48 99.77 0.0028 0.23 Comparative Example 3 28.41 99.96 0.0028 0.032
[0087] As can be seen from Table 2, compared with Examples 4 and 5, the molar ratio of the copper source, carbon source and nitrogen source in Example 1 is 2.5:1:3, and the molar ratio of the carbon source and nitrogen source in the catalyst carrier is 3.5:1. The molar ratios of the copper source, carbon source and nitrogen source in Examples 3 and 4 are 2.5:1:1.5 and 2.5:1:4.5, and the molar ratios of the carbon source and nitrogen source in the catalyst carrier are 1:1.5 and 1:4.5. It can be seen that if the nitrogen source content in the catalyst carrier is too high or too low, the active metal particles will gradually increase, resulting in a decrease in the dispersibility of the catalyst and a decrease in the catalyst's selectivity for hydrogen. An appropriate amount of nitrogen in the catalyst can not only promote copper dispersion, but also fix the valence of copper, thereby promoting the methanol liquid phase reforming hydrogen production reaction and increasing the catalytic hydrogen production rate.
[0088] Compared with Example 1, when other conditions remain unchanged, the copper-based catalyst prepared in Example 1 does not add a nitrogen source, but only uses a carbon source as a carrier. The active substance Cu has poor dispersibility on the carbon carrier and agglomerates, and there is no nitrogen on the catalyst carrier to fix the valence of copper, so that the catalytic hydrogen production rate decreases rapidly. Compared with Example 2, when other conditions remain unchanged, the carrier of the copper-based catalyst provided in Example 2 is all citric acid, and there is no nitrogen source in the carrier, so that the active metal Cu cannot be evenly distributed on the carbon carrier, resulting in Cu agglomeration, and the active metal particle size increases rapidly, resulting in poor catalyst dispersibility, resulting in a rapid decrease in the catalytic hydrogen production rate.
[0089] The above experimental results show that the preparation method of the present application synthesized nitrogen-doped carbon-coated copper nanocatalysts by the sol-gel method. Using a carbon source combined with a nitrogen source as a carrier, nitrogen doping not only promotes the dispersion of copper, but also improves the catalyst's selectivity for hydrogen and reduces the content of methane and carbon monoxide in the product. The highly dispersed Cu-based catalyst exhibits high activity, high stability, and low cost in the process of hydrogen production by liquid phase reforming of methanol, can reduce the temperature of hydrogen production by liquid phase reforming, and realizes efficient hydrogen production by liquid phase reforming of methanol and water.
[0090] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A highly dispersed nitrogen-doped copper-based catalyst comprising a carrier and an active metal component supported on the carrier, characterized in that: The carrier of the copper-based catalyst is composed of carbon, and the active metal component is Cu; the loading amount of the active metal component Cu is 30wt% to 60wt%.
2. The highly dispersed nitrogen-doped copper-based catalyst according to claim 1, characterized in that: The molar ratio of the carbon source to the nitrogen source in the carrier of the copper-based catalyst is 1:(1.5-6).
3. The highly dispersed nitrogen-doped copper-based catalyst according to claim 1, characterized in that: The average particle size of copper in the copper-based catalyst is 2 to 10 nm.
4. The method for preparing the highly dispersed nitrogen-doped copper-based catalyst according to claim 1, characterized in that: The following steps are involved: S1. Dissolve the copper source, carbon source, and nitrogen source in proportion to form a mixed solution, stir evenly and evaporate the solvent, and dry to obtain a highly dispersed nitrogen-doped copper-based catalyst precursor; The molar ratio of the copper source, the carbon source and the nitrogen source in the mixed solution is: 2.5:1:(1.5-6); S2. subjecting a highly dispersed nitrogen-doped copper-based catalyst precursor to a pyrolysis treatment at 300 to 500° C. for 2 to 5 hours; and then subjecting the pyrolysis-treated catalyst precursor to an activation treatment in a reducing atmosphere to obtain the highly dispersed nitrogen-doped copper-based catalyst.
5. The method for preparing a highly dispersed nitrogen-doped copper-based catalyst according to claim 4, characterized in that: The copper source described in S1 is one or more of copper nitrate, copper chloride, copper sulfate, and copper acetate.
6. The method for preparing a highly dispersed nitrogen-doped copper-based catalyst according to claim 5, characterized in that: The carbon described in S1 is one or more of starch, glucose, cyclodextrin and citric acid.
7. The method for preparing a highly dispersed nitrogen-doped copper-based catalyst according to claim 5, characterized in that: The nitrogen source described in S1 is one or more of ornithine, glycine, citrulline and arginine.
8. The method for preparing a highly dispersed nitrogen-doped copper-based catalyst according to claim 5, characterized in that: The activation treatment under reducing atmosphere in S2 is to reduce the highly dispersed nitrogen-doped copper-based catalyst precursor after pyrolysis treatment at 300° C. for 2 hours in a hydrogen atmosphere; the hydrogen flow rate is 50 mL / min.
9. The highly dispersed nitrogen-doped copper-based catalyst according to claim 1 is used to catalyze the liquid phase reforming of alcohols to produce hydrogen.
10. A liquid phase reforming reaction for producing hydrogen from alcohols, characterized in that: Weigh the catalyst and place it in the inner lining of the reactor, add 20 mL of alcohol aqueous solution, fill with nitrogen and pressurize to 2 MPa, repeat the gas washing three times to ensure that the air is completely removed, and then heat the reaction at 210°C and 2 MPa N2 atmosphere for 1 hour. After the reaction, collect the gas in the reactor with an air bag and determine the hydrogen production by gas chromatography.
Citation Information
Cited By
Nitrogen-doped carbon-coated copper catalyst and preparation method thereof, and method for preparing nitrile through aldehyde ammoxidation
CN120189966A
Method for producing hydrogen by catalyzing methanol steam reforming at low temperature
CN121158733A
Monatomic copper catalyst, its preparation method and application
CN122850156A
